THE STUDY OF RUNNING EFFICIENCY OF MORTAR PUMP BALL VALVES ACCORDING TO THE MOTION LAW OF PISTON (Academic journal Industrial Machine Building Civil Engineering, 2017)
There has been examined the effect of changing the motion law of piston in a differential mortar pump on the amount of lossesof construction mortar mix of the injectionvalve which operates at closing. Keywords:differential mortar pump, piston, the law of motion, valve.